An analytical study on low voltage regime of natural organic semiconductor based device: Physics of trap energy and ideality factor. (January 2021) - Chakraborty, K.; Das, A.; Mandal, R.; Mandal, D.K.
Abstract: Present investigation demonstrates the physics at low voltage region of natural organic semiconductor based single layer device. Theoretical explanation of diffusion driven current equations has been implemented as an efficient way to study the charge transport mechanism in that regime. GPVDM (abbreviated form of General purpose photovoltaic model), a renowned software simulation technique of organic devices has been introduced to obtain current voltage relationship and fitted with diffusion assisted equation. The plot shows high consistency with theoretical explanation which indicates reliability of the plot. Simulation based observation on trap assisted conduction at low voltage and its relation with corresponding ideality factor at that region has been explained on the basis of theoretical point of view. It has been found that ideality factor decays exponentially with increasing trap energy at low voltage. Experimental approach has finally been employed on Turmeric and Indigo dye based single layer natural semiconducting diodes to validate the outcome of the proposal. Results of the experiment lead to great similarity with the outcomes of both theoretical and simulation approach. Highlights: Diffusion dominated conduction mechanism of at low voltage has been reported. Theoretical aspect has been explained and simulation modeling has been introduced to validate the approach. Simulation techniques give quite interesting result and have good consistency together with theoretical concept. Based on simulation result, further study has been executed to relate the dependence of ideality factor and trap energy. Experimental approach has been undertaken on a pair of natural organic dye based devices to verify the reliability of the prediction.